The Swedish Corporate Control Model: Convergence, Persistence or Decline? - Magnus Henrekson; Ulf Jakobsson (Research Institute of Industrial Economics (IFN), 2011)
This paper explores the effects of deregulation and globalization on the dominant mode of corporate governance in Swedish public firms. The effects are multidimensionalthe direction of change in corporate governance cannot be determined by simply examining whether a convergence towards the Anglo-Saxon model is occurring. Dispersed ownership with management control has not proven to be a viable model of corporate governance for Swedish listed companies. Instead, the control models with the most rapid growth in the most recent decades are found outside the stock market, notably private equity and foreign ownership. After a major revival of the Swedish stock market its importance for the Swedish economy is again in decline. Instead of adjustments in pertinent institutions and practices to ensure effectiveness of the corporate governance of Swedish public firms under these new conditions, a great deal of endogenous adjustment of the ownership structure has taken place.
Keywords: M13; N24; O38; P16; 330; Corporate control; Corporate governance; Corporatism; Entrepreneurship; Ownership policy; Ownership structure; Swedish model; Corporate Governance; Eigentümerstruktur; Industriepolitik; Korporatismus; Schweden